60.6k views
0 votes
What is the first step in solving In(x - 1) = In6 - Inx for x?

2 Answers

4 votes

Explanation:

The first step is to create the domain of this equation.


\ln(x-1)=\ln6-\ln x\\\\D:\ x-1>0\ \wedge\ x>0\\\\x>1\ \wedge\ x>0\Rightarrow x>1


\ln(x-1)=\ln6-\ln x\qquad\text{use}\ \log_ab-\log_ac=\log_a(b)/(c)\\\\\ln(x-1)=\ln(6)/(x)\iff x-1=(6)/(x)\\\\(x-1)/(1)=(6)/(x)\qquad\text{cross multiply}\\\\x(x-1)=(1)(6)\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(x)(x)+(x)(-1)=6\\\\x^2-x=6\qquad\text{subtract 6 from both sides}\\\\x^2-x-6=0\\\\x^2+2x-3x-6=0\\\\x(x+2)-3(x+2)=0\\\\(x+2)(x-3)=0\iff x+2=0\ \vee\ x-3=0\\\\x+2=0\qquad\text{subtract 2 from both sides}\\x=-2 \\otin D\\\\x-3=0\qquad\text{add 3 to both sides}\\x=3\in D

Solution:

x = 3

User Alexander Measure
by
5.0k points
3 votes

Answer:

The first step would to be use quotient rule.

3

Explanation:

ln(x-1)=ln(6)-ln(x)

The first step would to be use quotient rule there on the right hand side:

ln(x-1)=ln(6/x)

*Quotient rule says ln(a/b)=ln(a)-ln(b).

Now that since we have ln(c)=ln(d) then c must equal d, that is c=d.

ln(x-1)=ln(6/x)

implies

x-1=6/x

So you want to shove a 1 underneath the (x-1) and just cross multiply that might be easier.


(x-1)/(1)=(6)/(x)

Cross multiplying:


x(x-1)=1(6)

Multiplying/distribute[/tex]


x^2-x=6

Subtract 6 on both sides:


x^2-x-6=0

Now this is not too bad to factor since the coefficient of x^2 is 1. All you have to do is find two numbers that multiply to be -6 and add up to be -1.

These numbers are -3 and 2 since -3(2)=-6 and -3+2=-1.

So the factored form of our equation is


(x-3)(x+2)=0

This implies that x-3=0 or x+2=0.

So solving x-3=0 gives us x=3 (just added 3 on both sides).

So solve x+2=0 gives us x=-2 (just subtracted 2 on both sides).

We need to see if these are actually the solutions by plugging them in.

Just a heads up: You can't do log(negative number).

Checking x=3:

ln(3-1)=ln(6)-ln(3)

ln(2)=ln(6/3)

ln(2)=ln(2)

This is true.

Checking x=-2:

ln(-2-1)=ln(6)-ln(-2)

ln(-3)=ln(6)-ln(-2)

We don't need to go further -2 makes the inside of our logarithms negative above.

The only solution is 3.

User Mikelegg
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.